Answer:
v = √(Lsinθ tanθ)
Step-by-step explanation:
From the diagram attached,
v = the tangential speed.
r = the radius of the horizontal circle.
T = tension in the string.
θ = the angle that the string makes with the vertical
m = Bob's mass (mg = the weight)
F = centripetal force
L = the length of the string
From geometry,
r = Lsin θ
Thus, the centripetal acceleration is given as;
a = v²/r = v²/Lsin θ
Force = mass x acceleration
Thus,
Centripetal force = mv²/Lsin θ
Let's balance the vertical forces to obtain,
T cosθ - mg = 0
Thus, T cosθ = mg - - - - (eq1)
Similarly, let's balance the horizontal forces to obtain;
T sinθ = F = mv²/Lsin θ
So, T sinθ = mv²/Lsin θ - - - - (eq2)
Let's divide eq 2 by eq 1 to get;
Tsinθ/Tcosθ = (mv²/Lsin θ)/mg
tanθ = gv²/Lsinθ
Thus, v² = Lsinθ tanθ
v = √(Lsinθ tanθ)